The role of T lymphocytes in ANCA associated vasculitis: neglected or revisited? - Kälsch, Anna-Isabelle; Woude, Fokko J. van der; Yard, Benito A. (Clinical nephrology, 2005)
"Antineutrophil cytoplasmic antibodies (ANCA) are pathogenic--Oh yes they are!" is the title of a recent review [Falk et al. 2002], discussing the current evidence on the pathogenic role of ANCA in vasculitis. But what about T lymphocytes? Do these cells also contribute to disease manifestation and if so to what extend? T-cells most likely play a role in delivering proper signals to autoreactive B cells for the production of ANCA, but, in the efferent arm of the immune response the involvement of T cells is less obvious and controversially discussed. Numerous studies provide evidence that peripheral T-cell phenotypes are dramatically changed in ANCA associated vasculitis (AAV) patients. How these changes relate to disease manifestation is still a matter of discussion. In an attempt to provide a better understanding of how T cells might play a role in AAV, the present paper will review recent data presented at the 12th international vasculitis and ANCA workshop.
Gesehen am 05.05.2022